Escrever para tornar a escuridão mais bonita : um estudo sobre a construção simbólica da morte em quatro romances angolanos - Minuzzi, Luara Pinto (2018)
This thesis proposes as a research theme the study of the construction of death from the symbology of the four fundamental elements – water, air, earth and fire – in Angolan novels published since the 1980s. The literary corpus will be formed by the following works: Mayombe (1980), by Pepetela; Mãe, materno mar (2001), by Boaventura Cardoso; Teoria geral do esquecimento (2012), by José Eduardo Agualusa and Os transparentes (2013), by Ondjaki. One can divide the books to be analyzed in two distinct ways: the first, in relation to the theme, divides the books that deal with the war of independence and with the moment of Independence (Mayombe and Teoria geral do esquecimento) and those dealing with Angola exclusively after the end of colonialism (Mãe, materno mar and Os transparentes); the second, related to the authors, places the two who lived the war of independence (Pepetela and Boaventura Cardoso) in opposition to those who did not live (Agualusa and Ondjaki). Thus, the objective is to analyze how the symbolic construction of death differentiates between these groups and how the war factor influences such construction. The central idea of this work is that there is a gradation between the four novels of the corpus in relation to the symbolic construction of death to be represented more as a transformation, as a new stage of life, or more as a definitive end: in the first extreme, that of death as a process, there is Mayombe, followed by Mãe, materno mar, Teoria geral do esquecimento and Os transparentes. The studies of Gaston Bachelard, Gilbert Durand, Northrop Frye, Carl Gustav Jung, Mircea Eliade, among others, will be used, concerning questions about symbols and the imaginary, as the theoretical basis of the research. Special attention will also be given to the theorists who deal with the situation in Africa and Angola and their histories, cultures and literatures, with studies by Pires Laranjeira, Inocência Mata, Ana Mafalda Leite, Kwame Anthony Appiah, Joseph Ki-Zerbo, etc.